Hydrogen to Deuterium Exchange Rate Measurement in Ionic Liquid-Water Mixture Using NMR - Singh, Balvinder (Asian Journal of Chemistry, 2021)
The rate of hydrogen (H) to deuterium (D) exchange in an aqueous system or bulk water is faster, making it challenging to estimate the rate of H to D exchange using nuclear magnetic resonance spectroscopy (NMR). Confined water behaves differently than bulk water in high viscous media, such as some room temperature ionic liquids and the H/D exchange rate becomes slow, which can be measured via NMR. Here, we used selective inversion recovery method to confined water in ionic liquid ([BMIM][BF4])-water-deuterium oxide mixture and measured exchange rate. The numerical value of exchange rate obtained using non-linear curve fitting of the experimental data is 1.34 s–1.